Designing Digital Microlearning Modules to Enhance Sigma Notation Conceptual Understanding and Computational Thinking in Calculus Learning - Enjun Junaeti; Nanang Priatna; Dadan Dasari; Tatang Herman (Journal of Education Technology, 2026)
Difficulties in learning calculus remain a major challenge for computer science students because abstract concepts and complex mathematical procedures frequently hinder analytical and computational reasoning abilities. This study aims to develop a digital microlearning module designed to support computer science education students in understanding sigma notation while strengthening their computational thinking skills. A research and development approach adopting the ADDIE framework was employed through analysis, design, development, implementation, and evaluation stages. The module was validated by one mathematics education expert and two computer science education experts specializing in multimedia before being implemented with 41 students. Data were collected through essay-based tests and student perception questionnaires addressing attention, emotional engagement, comprehension, and accessibility aspects. Findings revealed that most students successfully achieved the intended learning objectives, particularly in recognizing numerical patterns, constructing sigma notation expressions, and applying decomposition, pattern recognition, algorithmic thinking, and abstraction during problem-solving activities. Difficulties nevertheless remained in algebraic manipulation and evaluation of generalized summation forms. Students demonstrated positive perceptions toward the developed modules, especially regarding learning flexibility and support for independent learning. These findings indicate that digital microlearning has significant potential to support computational thinking–based calculus learning in computer science education.